Albert Ayler’s Ghost: A one-act play - Pillai, Nicolas (Jazz Research Journal, 2022)
This short play dramatizes the myth-making around a lost episode of the BBC’s Jazz Goes to College series—‘The Albert Ayler Quintet’ recorded by an Outside Broadcast unit at the London School of Economics on 15 November 1966. I use the event to explore questions of cultural ownership, institutional racism and academic hierarchy. The content of the play is based upon the archival, ethnographic and television production elements of my 2017–2019 Arts and Humanities Research Council project ‘Jazz on BBC-TV 1960–1969’ (AH/P007376/1). The play is an experiment in scholarly form, a challenge to the exclusionary structures of academia (including language) and an acknowledgment of the subjective and autobiographical impulses that inform historical narrative.